Novel Oxidation of 1,4-Dihydropyridines - Hatamjafari, Farhad; Montazeri, Nasser; Pourshamsian, Khalil (Asian Journal of Chemistry, 2011)
A one-pot method for the oxidation of 1,4-dihydropyridines to pyridines using magnesium bromide and hydrogen peroxide at convenient temperature in excellent yields has been described.